Comparative anatomy of elaiophores and oil secretion in the genus Gomesa (Orchidaceae) - Gomiz, Natalia Elva (2013)
Oils are atypical floral rewards in Orchidaceae, and are produced by epidermal glands called elaiophores. Flowers of many members of the sub-tribe Oncidiinae either produce oil or mimic oil-producing flowers of Malpighiaceae. We focus our research on three species of Gomesa, namely, G. flexuosa, G. riograndensis and G. varicosa in order to investigate the presence of elaiophores, their micromorphology and internal structure and the process of oil secretion. Elaiophores were located using Sudan III, and their internal and external features examined using light and scanning electron microscopy, respectively. The presence of elaiophores was confirmed for regions of calli that are prominent and exposed. In all three species, the secretory tissue comprised a single layer of epidermal cells, together with some parenchymatous, subsecretory cells. Epidermal cells were isodiametric or palisade-like, with dense cytoplasm, small vacuoles and prominent nuclei. Gomesa flexuosa differs from the other species investigated in that it bears intermediate elaiophores (i.e. epithelial and possessing unicellular, secretory trichomes). Based on the absence of a distended cuticle, we propose that oil possibly passes through the wall and cuticle as small lipid moieties. In addition, some evolutionary trends in the elaiophores in the genus Gomesa are suggested.